Effects of rubiadin-3-methyl ether on the immune properties of hUC-MSCs - Thi Sam, Nguyen; Thi Huyen, Nguyen; Phuong-Anh, Nguyen Thi; The Dan, Pham; Thuy-Ngan, Nguyen Thi; Manh Cuong, Nguyen; Hoang Ha, Chu; Trung Nam, `Nguyen (Vietnam Journal of Biotechnology, 2023)
Mesenchymal stem cells (MSCs) have become an effective tool for treating immune-related diseases due to their multilineage potential and immunomodulatory capabilities. One of the main factors contributing to their immunomodulatory capabilities is the IDO cascade, which was chosen as the main subject in this research. The IDO-Kyn-AHR-CYP cascade was chosen to evaluate the immunomodulatory properties of treated MSCs, with expression levels of the key gene IDO (indoleamine 2,3-dioxygenase) selected as the screening criterion. Cultured human umbilical cord MSCs (hUC-MSCs) were treated with different natural bioactive compounds. Preliminary results indicated that Rubiadin-3-methyl ether, an anthraquinone derivative isolated from the roots of Morinda longissima, was able to significantly induce IDO2 expression in UC-MSCs but not CYPs. This is the first study to show a link between Rubiadin-3-methyl ether and IDO2 in hUC-MSC. More research is needed to determine whether human UC-MSCs primed with Rubiadin-3-methyl ether have any significant benefits for treating immune-related diseases and disorders.